Self-objectification in women causes, consequences, and counteractions - Calogero, Rachel M.; Tantleff-Dunn, Stacey; Thompson, J. Kevin (Washington, D.C. American Psychological Association [2011], 2011)
"Modern industrialized society chronically and pervasively objectifies the female body, and many women have come to view themselves through the lens of an external observer, habitually monitoring their own appearance whether in public or private settings. Given the negative effects associated with self-objectification-such as body shame, appearance anxiety, depression, and disordered eating-an empirically based approach to researching and counteracting self-objectification is critical. This book integrates recent research developments and current clinical knowledge on self-objectification in women. Using Barbara L. Fredrickson and Tomi-Ann Roberts' objectification theory as a framework, the contributors address various aspects of the theory, including evidence for and causes of self-objectification across the life span, psychological consequences, and associated mental health risks. The book also discusses various scales for measuring self-objectification, as well as approaches to prevent and disrupt this phenomenon. With research from a variety of disciplines-psychology, sociology, anthropology, women's studies, and political science-this book should be read by everyone interested in the well-being of women"--Publicity materials. (PsycINFO Database Record (c) 2010 APA, all rights reserved)
Part I. Introduction and assessment -- ch. 1. Objectification theory : an introduction / Rachel M. Calogero, Stacey Tantleff-Dunn, and J. Kevin Thompson -- ch. 2. Operationalizing self-objectification : assessment and related methodological issues / Rachel M. Calogero -- Part II. Sexual and self-objectificaion -- ch. 3. The sexualization of girls and women as a primary antecedent of self-objectification / Linda Smolak and Sarah K. Murnen -- ch. 4. The birthmark : an existential account of the objectification of women / Jamie L. Goldenberg and Tomi-Ann Roberts -- ch. 5. Continuity and change in self-objectification : taking a life-span approach to women's experiences of objectified body consciousness / Nita Mary McKinley -- Part III. consequences of self-objectification -- ch. 6. Performance and flow : a review and integration of self-objectification research / Diane M. Quinn, Stephenie R. Chaudoir, and Rachel W. Kallen -- ch. 7. Mental health risks of self-objectification : a review of the empirical evidence for disordered eating, depressed mood, and sexual dysfunction / Marika Tiggemann -- Part IV. Prevention and disruption of sexual and self-objectification -- ch. 8. Embodying experiences and the promotion of positive body image: the example of competitive athletics / Jessie E. Menzel and Michael P. Levine -- ch. 9. Fighting self-objectification in prevention and intervention contexts / Tracy L. Tylka and Casey L. Augustus-Horvath -- Part V. Concluding remarks -- ch. 10. Future directions for research and practice / Rachel M. Calogero, Stacey Tantleff-Dunn, and J. Kevin Thompson.
Includes bibliographical references and index.
Keywords: Body image in women; Body image disturbance; Self-perception in women